Emergency contraception amongst female college students - knowledge, attitude and practice - Wendwosen T. Nibabe; Tennyson Mgutshini (AOSIS, 2014)
Background: Unwanted teenage pregnancies have a notable detrimental impact on the learners' trajectory and have been associated with jeopardising the students' educational progress and future career prospects. These pregnancies are mostly unplanned and unintended and many are terminated, either legally or illegally. Aim: The aim of this study was to explore the contributory role played by the knowledge, attitude and practices of female college students with respect to the utilisation of emergency contraceptives. Setting: Three tertiary institutions in Dessie, Ethiopia. Methods: Quantitative self-administered questionnaires were used to collect descriptive data from 352 female college students. Results: The study revealed that there was a high percentage (78.3%) of unwanted pregnancies amongst those engaging in sex. Significantly, nearly half (43.3%) of these unwanted pregnancies resulted in abortion. Only 10% of the students sampled admitted to ever having used emergency contraception. Even though more than half (69.9%) of the students knew about emergency contraception, only 27% of them felt confident that they understood when it was most effective. Conclusion: These and other observed findings confirm the need for improvement of female college students' knowledge and timely utilisation of emergency contraception.